Prenatal lead (Pb) exposure is associated with differential placental DNA methylation and hydroxymethylation in a human population. Issue 13 (9th December 2022) - Tung, Pei Wen; Kennedy, Elizabeth M.; Burt, Amber; Hermetz, Karen; Karagas, Margaret; Marsit, Carmen J.
ABSTRACT: Prenatal lead (Pb) exposure is associated with adverse developmental outcomes and to epigenetic alterations such as DNA methylation and hydroxymethylation in animal models and in newborn blood. Given the importance of the placenta in foetal development, we sought to examine how prenatal Pb exposure was associated with differential placental DNA methylation and hydroxymethylation and to identify affected biological pathways linked to developmental outcomes. Maternal (n = 167) and infant (n = 172) toenail and placenta (n = 115) samples for prenatal Pb exposure were obtained from participants in a US birth cohort, and methylation and hydroxymethylation data were quantified using the Illumina Infinium MethylationEPIC BeadChip. An epigenome-wide association study was applied to identify differential methylation and hydroxymethylation associated with Pb exposure. Biological functions of the Pb-associated genes were determined by overrepresentation analysis through ConsensusPathDB. Prenatal Pb quantified from maternal toenail, infant toenail, and placenta was associated with 480, 27, and 2 differentially methylated sites (q < 0.05), respectively, with both increases and decreases associated with exposure. Alternatively, we identified 2, 1, and 14 differentially hydroxymethylated site(s) associated with maternal toenail, infant toenail, and placental Pb, respectively, with most showing increases in hydroxymethylation with exposure. Significantly overrepresented pathways amongst genes associated with differential methylation and hydroxymethylation (q < 0.10) included mechanisms pertaining to nervous system and organ development, calcium transport and regulation, and signalling activities. Our results suggest that both methylation and hydroxymethylation in the placenta can be variable based on Pb exposure and that the pathways impacted could affect placental function.